Polyethylene Glycol: The Future of Posttraumatic Nerve Repair? Systemic Review - Paskal, Adriana; Paskal, Wiktor; Pietruski, Piotr; Wlodarski, Pawel (International journal of molecular sciences, 2019)
Peripheral nerve injury is a common posttraumatic complication. The precise surgical repair of nerve lesion does not always guarantee satisfactory motor and sensory function recovery. Therefore, enhancement of the regeneration process is a subject of many research strategies. It is believed that polyethylene glycol (PEG) mediates axolemmal fusion, thus enabling the direct restoration of axon continuity. It also inhibits Wallerian degeneration and recovers nerve conduction. This systemic review, performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, describes and summarizes published studies on PEG treatment efficiency in various nerve injury types and repair techniques. Sixteen original experimental studies in animal models and one in humans were analyzed. PEG treatment superiority was reported in almost all experiments (based on favorable electrophysiological, histological, or behavioral results). To date, only one study attempted to transfer the procedure into the clinical phase. However, some technical aspects, e.g., the maximal delay between trauma and successful treatment, await determination. PEG therapy is a promising prospect that may improve the surgical treatment of peripheral nerve injuries in the clinical practice.